1980
DOI: 10.3109/00365528009181432
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of the Colon in Calcium Absorption Following Small-Intestinal Resection

Abstract: The importance of the colon for the absorption of calcium, fat, and fluid was studied in 118 patients with small-bowel resections of various lengths. The patients fell into two groups: 38 with ileostomy and 80 with part of or the whole colon in function. In patients with ileostomy, but not in patients with the colon preserved, the absorption of 47Ca and fluid was inversely correlated to the length of the resected small intestine. In patients with extreme small-bowel resection (greater than or equal to 150 cm) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…Serum levels of Ca remained unchanged under all experimental conditions, both one month and three months after 50% DSI resection. Key Words nutritive utilization, intestinal resection, rat, calcium, femur, serum Calcium malabsorption is common in patients who have undergone massive resection of the small intestine (1). Factors contributing to the decrease in calcium absorption in these patients include malabsorption of dietary vitamin D and 25-hydroxyvitamin D as a result of the interruption of enterohepatic circulation (2,3) and an increase in fat excretion (steatorrhea) (1,4).…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of Ca remained unchanged under all experimental conditions, both one month and three months after 50% DSI resection. Key Words nutritive utilization, intestinal resection, rat, calcium, femur, serum Calcium malabsorption is common in patients who have undergone massive resection of the small intestine (1). Factors contributing to the decrease in calcium absorption in these patients include malabsorption of dietary vitamin D and 25-hydroxyvitamin D as a result of the interruption of enterohepatic circulation (2,3) and an increase in fat excretion (steatorrhea) (1,4).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of 1,25(OH)2D3 on growth in normal tissues has been less extensively studied. Birge and Alpers (6) found that repletion of vitamin D-deficient rats rapidly stimulated intestinal mucosal cell proliferation, which was associated with a 20% increase in villus cell number by 32 h. The colonic epithelium is of interest since it manifests both the classic and nonclassic actions of vitamin D. Colonic calcium absorption is vitamin D-responsive, and in some circumstances, such as the short bowel syndrome, may be important in calcium homeostasis (7,8). In addition, the effect of 1,25(OH)2D3 on colonocyte growth and differentiation is of particular interest in view of epidemiologic evidence suggesting that sunlight exposure and dietary vitamin D and calcium intake may influence the prevalence of colonic carcinoma (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Addressing this issue is of physiological importance because the colon has a unique structure, luminal environment, absorption mechanisms, and energy metabolism when compared with the small intestine. Folate uptake may also be of nutritional importance especially under conditions of massive disease or extensive resection of the small intestine (17)(18)(19)(20). Furthermore, studies of folate metabolism at the cellular level may help clarify the causes of the localized folate deficiency believed to be associated with premalignant changes in colonic epithelia (21,22).…”
mentioning
confidence: 99%